2015
DOI: 10.1158/1535-7163.mct-15-0140
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Induces Tumor Growth and Chemoresistance through Activation of the PI3K/Akt/mTOR Pathway in Bladder Cancer

Abstract: Continued smoking is highly associated with not only a higher incidence but also greater risk of tumor recurrence, progression, and acquired chemoresistance of urothelial carcinoma. We investigated whether nicotine affects urothelial carcinoma, and the detailed mechanism by which nicotine could induce tumor growth and any associated chemoresistance. Cell viability was evaluated in the human bladder cancer cell line T24 exposed to nicotine with or without cisplatin (CDDP) and NVP-BEZ235 as a PI3K/mTOR dual inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 42 publications
6
47
1
Order By: Relevance
“…Nicotine had the strongest effect on VPS33B expression at a concentration of 10 μmol/l after 96 hr. Previous reports have emphasized that nicotine promotes malignant phenotype in cervical carcinoma and bladder cancer via regulating the PI3K/AKT pathway . As shown in Figure d , nicotine suppressed the protein level of p‐PI3K, p‐AKT, c‐Jun and VPS33B in CRC cells.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Nicotine had the strongest effect on VPS33B expression at a concentration of 10 μmol/l after 96 hr. Previous reports have emphasized that nicotine promotes malignant phenotype in cervical carcinoma and bladder cancer via regulating the PI3K/AKT pathway . As shown in Figure d , nicotine suppressed the protein level of p‐PI3K, p‐AKT, c‐Jun and VPS33B in CRC cells.…”
Section: Resultsmentioning
confidence: 69%
“…Previous reports have emphasized that nicotine promotes malignant phenotype in cervical carcinoma and bladder cancer via regulating the PI3K/AKT pathway. 17,18 As shown in Figure 1d, nicotine suppressed the protein level of p-PI3K, p-AKT, c-Jun and VPS33B in CRC cells. Interestingly, we observed that c-Jun bound to the promoter of VPS33B by bioinformation software (Supporting Information Fig.…”
Section: Vps33b Is Downregulated By Chemical Carcinogens and Poorly Ementioning
confidence: 87%
“…However, inhibition of p38 MAPK decreased BUC proliferation, growth, and cell invasiveness of bladder cancer via the MAPK pathway 55,56. Previous studies have demonstrated that activation of the PI3K-AKT–mechanistic target of rapamycin (mTOR) pathway promotes bladder carcinogenesis and, further, induces tumor growth and chemoresistance by nicotine 57,58. Moreover, activation of the PI3K-AKT–mTOR pathway is correlated with advanced tumor progression and unfavorable survival outcomes 59.…”
Section: Discussionmentioning
confidence: 99%
“…MDR1 and BCRP belong to efflux transporters of the ATP-binding cassette family and pumps many foreign substances out of cells [24]. Chemoresistance is induced or acquired through the activation of the PI 3 K /Akt/mTOR pathway in some malignancies [25]. Taken together, BTG3-mediated chemosensitivity was positively linked to the down-regulated expression of the chemoresistance-related genes.…”
Section: Discussionmentioning
confidence: 99%